Deep Learning-Based Diagnosis of Fatal Hypothermia Using Post-Mortem Computed Tomography - Zeng, Yuwen; Zhang, Xiaoyong; Yoshizumi, Issei; Zhang, Zhang; Mizuno, Taihei; Sakamoto, Shota; Kawasumi, Yusuke; Usui, Akihito; Ichiji, Kei; Bukovsky, Ivo; Funayama, Masato; Homma, Noriyasu (Tohoku journal of experimental medicine, 2023)
In forensic medicine, fatal hypothermia diagnosis is not always easy because findings are not specific, especially if traumatized. Post-mortem computed tomography (PMCT) is a useful adjunct to the cause-of-death diagnosis and some qualitative image character analysis, such as diffuse hyperaeration with decreased vascularity or pulmonary emphysema, have also been utilized for fatal hypothermia. However, it is challenging for inexperienced forensic pathologists to recognize the subtle differences of fatal hypothermia in PMCT images. In this study, we developed a deep learning-based diagnosis system for fatal hypothermia and explored the possibility of being an alternative diagnostic for forensic pathologists. An in-house dataset of forensic autopsy proven samples was used for the development and performance evaluation of the deep learning system. We used the area under the receiver operating characteristic curve (AUC) of the system for evaluation, and a human-expert comparable AUC value of 0.905, sensitivity of 0.948, and specificity of 0.741 were achieved. The experimental results clearly demonstrated the usefulness and feasibility of the deep learning system for fatal hypothermia diagnosis.
Keywords: Deep Learning; Humans; hypotermie; lidé; deep learning; Autopsy; pitva; Hypothermia; příčina smrti; Forensic Pathology; Cause of Death; soudní patologie; Tomography, X-Ray Computed; počítačová rentgenová tomografie